Post-transplant trajectories of the CRP-to-albumin ratio identify a late-emerging high-risk phenotype in interstitial lung disease - Ekaterina Krauss; Silke Tello; Luise Wilke; Janine Sommerlad; Gani Oruqaj; Natascha Sommer; Martin Reichert; Andreas Hecker; Anita Windhorst; Matthias Hecker; Andreas Guenther; Sabina A. Guler; et al. (BMC Pulmonary Medicine, 2026)
Abstract Background After bilateral lung transplantation for interstitial lung disease (ILD), most recipients recover well, but some deteriorate over the following years. The C-reactive protein–to–albumin ratio (CAR) combines a marker of systemic inflammation (CRP) with one of nutritional and hepatic-synthetic reserve (albumin); a rising ratio reflects worsening inflammation against falling reserve. We assessed whether tracking CAR over time identifies the subgroup at risk. Methods We studied 138 consecutive adult ILD recipients of bilateral lung transplants (Giessen, 2000 to 2026), with a median of 13 paired CRP and albumin measurements each. Using group-based trajectory modelling, we grouped patients by the trajectory of their CAR from the first routine follow-up visit (month 4) to year 5, then related the groups to five-year survival and the Clinical Frailty Scale (CFS). Results Three CAR trajectories emerged. Most patients were stable-low (39%, CAR near zero throughout) or resolving (38%, initially high then falling). The key group was CAR-rising (23%): at four months these patients were indistinguishable from the best-recovering stable-low group but then climbed steadily over the following years. Five-year survival was 92%, 61% and 69% in the stable-low, rising and resolving groups (log-rank p = 0.029; rising versus stable-low hazard ratio 4.5, 95% CI 1.2 to 17.1). A landmark analysis among patients alive at year 2 confirmed this late risk: 33% of the rising group died over the next three years versus 5% of the stable-low group ( p = 0.005). In the pre-specified model, phenotype membership was not predicted by ILD subtype or LAS at listing (likelihood-ratio p = 0.16); pre-transplant CAR itself differed modestly across the groups ( p = 0.049) but was not prognostic for survival. The CFS trajectory, scored independently of CRP and albumin, showed the same pattern: groups were equally frail before transplant ( p = 0.83) but separated afterwards ( p = 0.01 at 4 months, p = 0.001 at 5 years), the adverse groups drifting back toward frailty. Conclusions A simple test already measured at every post-transplant visit, the CRP-to-albumin ratio, can be read as a trajectory to identify the ILD recipients who enter an inflammatory and nutritional decline associated with worse five-year survival. These findings are hypothesis-generating, and further work is needed to establish what drives the CAR trajectory before any clinical application. Trial registration The analysis draws on two registries: the European IPF Registry and Biobank (eurIPFreg; ClinicalTrials.gov NCT02951416, registered 1 November 2016) and the European ILD Registry and Biobank (eurILDreg; German Clinical Trials Register DRKS00028968, registered 26 July 2022).